How to Transition the National Broadband Network to Fibre To The Premises - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2019)
NBN Co, the government business enterprise rolling out the National Broadband Network (NBN) adopted the Coalition Government’s Multi-Technology Mix (MTM) plan upon receipt of a revised Statement of Expectations following the September 2013 Federal election. The MTM NBN plan included rolling out the outdated Fibre to the Node technology and remediating and upgrading the existing Telstra and Optus Hybrid Fibre Coaxial networks. This paper discusses the migration from the MTM NBN to a Fibre to the Curb or ubiquitous Fibre to the Premises (FTTP) NBN. The paper also discusses the MTM NBN cost blowout, delays and rationale for the MTM NBN to be immediately replaced with a future-proof FTTP NBN.